APPLICATION OF FUZZY SET METHODS FOR MAKING MANAGEMENT DECISIONS IN CRISIS CONDITIONS - HEIDAROVA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The possibility of forecasting the results of management decision-making using the methods of linguistic vector evaluations, fuzzy logical conclusion, fuzzy relation of preferences, maximin convolution is considered. The method of applying the methods of linguistic vector evaluations, fuzzy logical conclusion, fuzzy relation of advantages, maximum convolution evaluation of possible values of management decisions in conditions of uncertainty (crisis). It was determined that the application of this method, with a simpler mathematical apparatus, allows to evaluate the possible variants of the values of management decisions with quality input parameters in crisis conditions. The technology of applying the maximin convolution method, the method of fuzzy preference ratio was studied, and a comparison of the method of fuzzy logical inference and linguistic vector estimates was made. The main advantages of using each of the above methods in making management decisions have been revealed. Disadvantages (limitations) regarding the use of the specified methods are identified.